Ad Criteria Of Criminalization - Salman Luthan (Fakultas Hukum Universitas Islam Indonesia, 2009)
In the criminalization, there are three primary principles need to be considered; legality, subsidiary, and equality before the law. There are also criteria to be taken into account; the act shall be in contravention with the sense of justice of the people, the ability of the existing legal framework to cater such act, the balance between the instruments required and the outcomes, the balance between the cost and benefit of the criminalization, the effect of such criminalization, and the last is the ability of the judicial system to enforce the law on the criminalized act.Keywords: Basic principle, Criminalization, Criminal Law